MicroRNAs as Important Players and Biomarkers in Oral Carcinogenesis. (4th October 2015) - Min, Anjie; Zhu, Chao; Peng, Shuping; Rajthala, Saroj; Costea, Daniela Elena; Sapkota, Dipak
Abstract : Oral cancer, represented mainly by oral squamous cell carcinoma (OSCC), is the eighth most common type of human cancer worldwide. The number of new OSCC cases is increasing worldwide, especially in the low-income countries, and the prognosis remains poor in spite of recent advances in the diagnostic and therapeutic modalities. MicroRNAs (miRNAs), 18–25 nucleotides long noncoding RNA molecules, have recently gained significant attention as potential regulators and biomarkers for carcinogenesis. Recent data show that several miRNAs are deregulated in OSCC, and they have either a tumor suppressive or an oncogenic role in oral carcinogenesis. This review summarizes current knowledge on the role of miRNAs as tumor promotors or tumor suppressors in OSCC development and discusses their potential value as diagnostic and prognostic markers in OSCC.